Evaluation of Antioxidant and Antibacterial Activity of Red Onion (A.CEPA L.) and Garlic (A.SATIVUM L.) Wastes on Homemade Tofu - Savitha Harivananthan; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2024)
In this study, 70% of the ethanolic extraction method was used to extract natural antioxidants from red onion (A.cepa) and garlic (A.sativum) wastes. The main purpose of this study is to compare the antioxidant activity from red onion (A.cepa), garlic (A.sativum) wastes and BHA to act as a preservative in tofu. The extract was characterized by its total phenolic content and antioxidant activity using Folin-Ciocalteau reagent and DPPH radical scavenging method, respectively. Current results of total phenolic content (TPC) assay indicate that TPC is higher in red onion (0.446 ± 0.321 mg GAE/g) as compared to garlic (0.231± 0.043 mg GAE/g). However, garlic husk shows a higher free radical scavenging activity which is (49.891 ± 0.143) compared to red onion peel (20.087 ± 0.041 %). The primary antioxidant activities of both the samples are lower than the standard antioxidant, BHA. The optimized extracts were further characterized for antibacterial activity against Escherichia coli (E.coli) and Staphylococcus epidermidis (S.epidermidis) by Kirby-Bauer agar disc diffusion method. The optimized extract shows a high degree of antibacterial activity against E.coli. After that, Fourier-transform infrared spectroscopy (FTIR) was used to analyze the presence of antioxidant compounds in red onion (A.cepa) and garlic (A.sativum) waste extracts. Next, the herbs of red onion, garlic and BHA were directly applied in liquid form to act as a preservative in homemade tofu. The stability of the tofu was identified according to the set time of total 14 days interval. For the antimicrobial activity, the tofu was observed by how much mould and fungal were developed and grown throughout the 14 days of storage. In conclusion, red onion and garlic can be successfully employed to improve the antioxidant properties of tofu and provide sustained antioxidants during storage although BHA still shows the best result as antioxidant.